2023
DOI: 10.3389/fpls.2023.1132959
|View full text |Cite
|
Sign up to set email alerts
|

RNA methylation in plants: An overview

Abstract: RNA methylation is an important post-transcriptional modification that influences gene regulation. Over 200 different types of RNA modifications have been identified in plants. In animals, the mystery of RNA methylation has been revealed, and its biological role and applications have become increasingly clear. However, RNA methylation in plants is still poorly understood. Recently, plant science research on RNA methylation has advanced rapidly, and it has become clear that RNA methylation plays a critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 80 publications
3
45
0
Order By: Relevance
“…RNA m 6 A modification was also found to be markedly increased throughout brain development . For plant growth, PtrMTA is responsible for the formation of m 6 A in poplar and regulate the root development and the tolerance of drought stress. Hormone responses related modified RNAs express more actively than the non-modified ones with increased m 6 A levels during tomato fruit expansion.…”
Section: Roles Of Rna Methylation In Developmentmentioning
confidence: 94%
“…RNA m 6 A modification was also found to be markedly increased throughout brain development . For plant growth, PtrMTA is responsible for the formation of m 6 A in poplar and regulate the root development and the tolerance of drought stress. Hormone responses related modified RNAs express more actively than the non-modified ones with increased m 6 A levels during tomato fruit expansion.…”
Section: Roles Of Rna Methylation In Developmentmentioning
confidence: 94%
“…Epitranscriptome comprises over 170 RNA modifications, with N6-adenine methylation (m6A) being the most extensively studied and abundant in eukaryotes, particularly in mRNA (Shinde et al, 2023). In the model plant Arabidopsis thaliana , m6A is deposited by a complex of methyltransferases mRNA adenosine methylase A (MTA, homolog of mammalian METTL3) and methyltransferase B (MTB, homolog of mammalian METTL14), along with cofactors VIRILIZER (VIR, homolog of mammalian VIRMA), E3 ubiquitin ligase AtHAKAI (homolog of mammalian HAKAI) and FKBP12 INTERACTING PROTEIN 37 (FIP37, homolog of mammalian WTAP) (Růžička et al, 2017; Shen, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the model plant Arabidopsis thaliana , m6A is deposited by a complex of methyltransferases mRNA adenosine methylase A (MTA, homolog of mammalian METTL3) and methyltransferase B (MTB, homolog of mammalian METTL14), along with cofactors VIRILIZER (VIR, homolog of mammalian VIRMA), E3 ubiquitin ligase AtHAKAI (homolog of mammalian HAKAI) and FKBP12 INTERACTING PROTEIN 37 (FIP37, homolog of mammalian WTAP) (Růžička et al, 2017; Shen, 2023). In mRNA, m6A is deposited at the RRACH (R = A/G, H = A/U/C) consensus motif, and is mostly prevalent near start/stop codons and at 3’ untranslated regions (3′-UTRs) of mature mRNAs (Shinde et al ., 2023). Several studies in different eukaryotic systems have shown that m6A modulates mRNAs fate in cells, by affecting mRNA stability and half-life, alternative splicing, mRNA translation, nucleo-cytoplasmic export rates, and m6A-mediated phase separation (Zaccara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also reported photosynthesis, plant hormone signal transduction, and mitogen-activated kinase signaling as a drought-responsive pathway [ 10 ]. The function of several abiotic-stress-responsive genes and small RNAs has been studied in several plants [ 11 ] and pearl millet [ 12 , 13 , 14 , 15 , 16 ]. However, knowledge of molecular mechanisms regulating physiological responses is equally critical and important for ensuring the quality and yield of plants.…”
Section: Introductionmentioning
confidence: 99%